1988
DOI: 10.1007/bf00146396
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of influenza A and B viruses in Italy between 1984 and 1987

Abstract: Antigenically heterogeneous strains and new variants of influenza A viruses, both A (H3N2) and (H1N1) subtypes, as well as influenza B strains were detected in Italy in a period, between 1984-1987, characterized by a moderate degree of influenza activity. Each year the evaluation, by SRH technique, of antibodies, in the population, to currently circulating viruses, has confirmed the extent of infection and often the prevalent virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…To check the immune level against the influenza A(H1N1) subtype we used the A/Taiwan/1/86 strain, which was not isolated during the winter 1987/88, but was the most prevailing virus during the previous influenza season (8). This influenza variant was selected as a vaccine component for the following winter 1988/89 (15).…”
Section: Antibody Surveysmentioning
confidence: 99%
See 2 more Smart Citations
“…To check the immune level against the influenza A(H1N1) subtype we used the A/Taiwan/1/86 strain, which was not isolated during the winter 1987/88, but was the most prevailing virus during the previous influenza season (8). This influenza variant was selected as a vaccine component for the following winter 1988/89 (15).…”
Section: Antibody Surveysmentioning
confidence: 99%
“…As in previous winters (8), the antigenic characterization of the isolates has shown that influenza A and B viruses, and often both, circulate every winter. Their presence has usually been associated with antigenic variation of the surface antigens.…”
Section: The Pattern Of Antibody In the Sera Collected In The Summer mentioning
confidence: 99%
See 1 more Smart Citation